ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE WEBSITE EFORM BNI KUR DENGAN METODE SYSTEM USABILITY SCALE - Romie Aswari (2023)
PT. Bank Negara Indonesia (Persero) Tbk is one of the companies engaged in the banking sector, especially in the KUR (People's Business Credit) Program sector which is intended to strengthen business capital capabilities in the framework of implementing policies to accelerate the development of the real sector and empower UMKM. PT. Bank Negara Indonesia (Persero) Tbk was established on July 5, 1946. To maximize the functions and objectives of PT. Bank Negara Indonesia (Persero) Tbk utilizes various types of media, both digital and conventional, to reach a wider market. The website-based information system is one of the media used by PT. Bank Negara Indonesia (Persero) Tbk to be able to serve customers so they can invest in the KUR program through PT. Bank Negara Indonesia (Persero) Tbk. Based on survey data "Use of the BNI eForm website in the KUR Registration Submission Process" as many as 67 respondents on average complained about the ease and convenience of using the website, therefore the researcher re-evaluated the BNI eForm website regarding the value of usability and user interface. This study aims to provide an assessment of the user experience and redesign the appearance of the user interface that is able to meet the usability level of the website-based BNI KUR eForm using the User Centered Design (UCD) approach. The application of the UCD method is carried out by carrying out questionnaires and prototyping with the System Usability Scale testing technique. This research will produce a new interface in the form of a prototype that can be used as a suggestion for improving the appearance of the BNI KUR eForm website. In the analysis of the running system interface display, after testing using the System Usability Scale method for the BNI KUR eForm website, an average score of 54 was obtained, which means that the usability or usability value of the BNI KUR eForm website cannot be said to be acceptable. After the redesign process was carried out by applying the Ucer Centered Design approach and re-testing the prototype resulting from the redesign of the interface display using the System Usability Scale, the average score was obtained which increased to 79 and can be said to be successful or acceptable. Keywords: Interface, Prototype, SUS, UCD, Customers